Association of Suicide Attempts and Non-Suicidal Self-Injury Behaviors With Substance Use and Family Characteristics Among Children and Adolescents Seeking Treatment for Substance Use Disorder - Guvendeger Doksat, Neslim; Zahmacioglu, Oguzhan; Ciftci Demirci, Arzu; Kocaman, Gizem Melissa; Erdogan, Ayten (Substance use & misuse, 2017)
Background: Numerous studies in youth and adults suggest strong association between substance use disorders and non-suicidal self-injury (NSSI) and suicidal behaviors. There is paucity of studies exploring the association of substance use with history of suicide attempts (HSA) and NSSI in children and adolescents in Turkey. Objective: We aimed to examine the prevalence of NSSI and HSA and their relationship with substance use and family characteristics among youth seeking treatment for substance use in Turkey. Method: Participants were children and adolescents who were admitted to the Bakirkoy Trainee and Research Hospital for Psychiatric and Neurologic Disorders in Istanbul between January 2011 and December 2013. Two thousand five hundred eighteen participants were included. Questionnaires were applied to all patients. The association of NSSI and HSA with substance use, family characteristics, and subject characteristics were analyzed. Results: The prevalence of NSSI and HSA behaviors among substance using youth in our sample were 52% and 21% respectively. Cannabis and cocaine use was found to be a significant risk factor for HSA, and polysubstance use was associated with both NSSI and HSA. Parental separation/divorce, parental mental disorders, alcohol and drug use, and crime were the risk factors for HSA. A positive history of physical and sexual abuse increased the risk of HAS, and a history of neglect increased the risk of NSSI. Conclusions/importance: We suggest that results showing relationship between substance use and associated social features with NSSI and HSA may contribute to elaborating effective and targeted preventive and intervention programs for these high-risk youth groups in Turkey.